2007
DOI: 10.1017/s1047951107001023
|View full text |Cite
|
Sign up to set email alerts
|

Motor development in children with congenital cardiac diseases compared to their healthy peers

Abstract: Their perceptual and motor experiences determine the physical and motor development of children, and impact also on their emotional, psychosocial, and cognitive development. Our aim, therefore, was to evaluate motor development in children with congenitally malformed hearts compared to their healthy peers. We compared 194 children, with a mean age of 10.0 years, and standard deviation of 2.7 years, representing the entire spectrum of congenital cardiac disease, to a control group of 455 healthy children, havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 41 publications
2
63
1
Order By: Relevance
“…Reported morbidities for patients after Fontan include deficits in motor development [3], inattention and hyperactivity [30], internalizing problems (depression, anxiety) and aggression [17], and hypoactive lifestyles [29]. The benefits of physically active lifestyles [13,15] are known to ameliorate many of the morbidities commonly experienced by patients after Fontan.…”
Section: Introductionmentioning
confidence: 99%
“…Reported morbidities for patients after Fontan include deficits in motor development [3], inattention and hyperactivity [30], internalizing problems (depression, anxiety) and aggression [17], and hypoactive lifestyles [29]. The benefits of physically active lifestyles [13,15] are known to ameliorate many of the morbidities commonly experienced by patients after Fontan.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to anatomic/hemodynamic risk factors, reduced physical activity may compromise the motor development of children with CHD (Bjarnason-Wehrens et al, 2007). Due to the heart disease medical restrictions may be imposed, exercise tolerance may be limited, and hospitalizations may cause periods of inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the illness may cause the parents to be anxious and overprotective toward the child (Samango-Sprouse & Suddaby, 1997), as a result of which they may limit its engagement in physical activity. Restrictions of physical activity, whether imposed by their cardiologist or their parents, may impede the motor development of children with CHD (Bjarnason-Wehrens et al, 2007). The motor slowness observed in these children may thus be due to a lack of sufficient practice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that abnormal hemodynamics during fetal gestation and hypoxia in utero might play an important role in the risk of long-term adverse neurological outcomes in children with critical CHD [9, 10]. A distinctive pattern of neurodevelopmental and behavioral impairments has been noticed over the years; these are characterized by delayed motor development, cognitive impairments, and other abnormal growth [11, 12]. Many school-aged survivors adapt poorly to their school life because of low physical activity levels and poor academic performance, and these problems may persist into young adulthood, leading to a low quality of life for these children and their families [13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrate that cardiac problems are not the only reason responsible for development delays [11, 1416]; overprotection of parents or main caregivers is also a factor. Parents are the most concerned caregivers for their children, and overprotection of children with CHD has been observed with most parents and teachers.…”
Section: Introductionmentioning
confidence: 99%